Adoption of Improved Dairy Farming Practices among Members and Non-members of Milk Co-operative Societies (Indian Journal of Extension Education, 2013)
The present investigation was carried out in Hanumangarh district of Rajasthan with 120 members and non-members of dairy cooperatives societies to find out adoption level of dairy farming practices. The study found that in case of member dairy farmers, majority of them (71.66%) possessed medium adoption level followed by low (16.67%) and high (11.67%) adoption level, respectively regarding improved dairy farming practices whereas, in case of non-member dairy farmers, majority belonged to medium adoption level (83.33%) followed by low (11.67%) and high (5.00%) adoption level, respectively regarding improved dairy farming practices. The study that indicated significant association of variables like social participation and extension contact with adoption level of both member and non member dairy farmers of MPCSs. Further, variables like milk production and milk consumption showed non significant association with adoption level.